Habilidades sociales en el proceso de aprendizaje de los estudiantes en la carrera de Pedagogía de las artes y humanidades de la Universidad Nacional de Chimborazo - Higuera Salas, Jorge Luis (2024)
The main objective of this research study was to analyze, identify and compare the development of social skills in first and seventh semester students of the Arts and Humanities Pedagogy program at the National University of Chimborazo. In theory, social skills are a set of cognitive-behavioral competencies that facilitate the human being to have positive, assertive relationships which are favorable with other human beings, within which can be seen, basic social skills such as: Active listening, thanking, greeting. In the advanced skills we can find: asking for help, participating, giving instructions, apologizing and convincing others. This research has a quantitative character, by the level is descriptive, by the basic objectives, by the place of field, by the cross-sectional time the population were the students of the career of Pedagogy of the arts and humanities of the National University of Chimborazo, the sample, was of a total of 56 students of first and seventh semester, The technique used was psychometric with the instrument of the Social Skills Scale EHS of Elena Gismero González, the results obtained after the data collection allowed to fulfill the objectives of the research, as for the interpretation of the data that was obtained was done through the Excel program making graphs that helped to a better interpretation. Of the first semester students of the Arts and Humanities Pedagogy course, it is understood that 16 students belonging to (52%) have an intermediate level regarding their social skills, as for the 15 students of the seventh semester belonging to (60%) it is understood that they have an intermediate level in the development of social skills.